CYCLIC OXONIUM IONS AND RELATED STRUCTURES - Gargiulo, Robert J. (1969)
This paper describes the preparation by several methods of trialkyloxonium ions containing five-membered rings and the study of their structures by observing the nuclear magnetic resonance (NMR) spectra in several solvents. This provides independent evidence for these compounds, whose existence has been shown by kinetic, preparative, and stereochemical studies. The following SbCl(6) oxonium salts have been prepared, isolated, and characterized as crystalline solids: the 1,2,5-trimethyltetrahydrofuranium (IIa), the 1,2,2,5-tetramethyl (IIb), the trans-1-methylperhydrobenzofuranium (IVa), the trans-1,2-dimethyl (IVb), and the trans-1,2,2-trimethyl (IVc) compounds. The trifluoroacetate salts IIc, IId, IVd, and IVe have been made in acid solution, and all the salts II and IV have been characterized by their NMR spectra as cyclic oxonium salts, with the charged 1-CH(3) group downfield from an uncharged —OCH(3). Spectra of all the SbCl(6) salts in nitrobenzene solution are reported. Further evidence for the cyclic structure is given by the identification of 2,2,5-trimethyltetrahydrofuran (VIII) from the action of pyridine and lithium chloride on the 1,2,2,5-tetramethyltetrahydrofuranium salt IIb. Solvolysis of this salt by ethanol gave 2-ethoxy-2-methyl-5-methoxyhexane (VII) by attack at the tertiary carbon of the oxonium ion. The structure of VII was established by its synthesis and that of the other possible isomer. The trifluoroacetate oxonium ion (IVe) gave, after three days in 5 per cent sulfuric-trifluoroacetic acid, trans-2,2-dimethylperhydrobenzofuran and methyl trifluoroacetate.